2013
DOI: 10.2466/29.22.pms.117x24z8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Music Tempo on Performance, Psychological, and Physiological Variables during 20 Km Cycling in Well-Trained Cyclists

Abstract: Few studies have investigated the effects of music on trained athletes during high intensity endurance tasks. Therefore, this study investigated the effects of different music tempi on performance, psychological, and physiological responses of well-trained cyclists to time trial cycling. 10 male road cyclists (M age = 35 yr., SD = 7), with a minimum of three years racing experience, performed four 20-km time trials on a Computrainer Pro 3D indoor cycle trainer over a period of four weeks. The time-trials were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
21
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 53 publications
3
21
2
Order By: Relevance
“…Coding for researcher-selected and self-selected music was generally unambiguous, although there were studies in which participants selected music tracks from a list provided by researchers (e.g., Ruscello, D'Ottavio, Padua, Tonnelli, & Pantanella, 2014) and others in which researchers selected tracks from a list provided by participants (e.g., Crust, 2004a;Dyer & McKune, 2013). In these instances, we considered the range of music choices available to participants, and coded the former cases as researcher-selected and the latter as self-selected.…”
Section: Search Resultsmentioning
confidence: 99%
“…Coding for researcher-selected and self-selected music was generally unambiguous, although there were studies in which participants selected music tracks from a list provided by researchers (e.g., Ruscello, D'Ottavio, Padua, Tonnelli, & Pantanella, 2014) and others in which researchers selected tracks from a list provided by participants (e.g., Crust, 2004a;Dyer & McKune, 2013). In these instances, we considered the range of music choices available to participants, and coded the former cases as researcher-selected and the latter as self-selected.…”
Section: Search Resultsmentioning
confidence: 99%
“…The results of the present study are consistent with those of previous studies that reported reduced RPE while listening to music. Nethery et al [ 20 ], Potteiger et al [ 7 ], Nethery [ 8 ], Yamashita et al [ 4 ], and Dyer and McKune [ 5 ] reported a decrease in RPE when listening to music while exercising. In contrast, Schwartz et al [ 10 ], Caria et al [ 21 ], Birnbaum et al [ 11 ], and Chtourou et al [ 22 ] did not find any significant differences in RPE when their subjects listened to music.…”
Section: Discussionmentioning
confidence: 99%
“…Of these musical qualities, the tempo and speed (bpm) are the easiest facets of music to manipulate . Several studies have found that music tempo aff ects performance ( Jarraya, Chtourou, Aloiui, Hammouda, Chamari, Chaouachi, et al ., 2012 ;Terry, Karageorghis, Saha, & D'Auria, 2012 ), whereas several other studies indicated no eff ect ( Mohammadzadeh, Tartibiyan, & Ahmadi, 2008 ;Dyer & McKune, 2013 ;Burket, Eubank, Reed, & Sanders, 2014 ). Inconsistent results can be explained by important methodological limitations verifi ed by Karageorghis and Priest (2012a) , such as choosing inappropriate measures to standardize music volume and controlling when the music will be played in relation to the task and using poor music-selection protocols.…”
mentioning
confidence: 94%
“…
Dyer and McKune (2013) stated that music tempo has no infl uence on performance, physiological, and psychophysical variables in well-trained cyclists during high intensity endurance tasks. However, there are important limitations in the methodology of the study.
…”
mentioning
confidence: 99%
See 1 more Smart Citation